The Relationship between Family Socio-economic Status and Health Financing Practices at Abdul Manap Hospital, Jambi City - Liza Syahputri; Dwi Noerjoedianto; Adila Solida (Lembaga Pengembangan Kinerja Dosen, 2022)
The provision of health services is one way to meet the needs and demands of the community for health, in the process including health financing. There are six financing patterns applied, one of which is out of pocket financing and Social Health Insurance Administration Body. The ability to buy health services depends on the readiness of the family to finance the household, so socioeconomic status influences the use of health financing patterns. This study uses quantitative methods with a cross-sectional research design. The population is the head of the family who seeks treatment at Abdul Manap Hospital, with as many as 89 respondents. Data collection using a questionnaire and data analysis using chi-square. Based on the analysis, the variables that have a relationship with the pattern of Social Health Insurance Administration Body financing are income (p-value 0.000), occupation (p-value 0.003), number of family members (0.028), and asset ownership (0.000). Meanwhile, the one that does not have a relationship is education (0.276). The conclusion of this study is that income, occupation, the number of family members, and asset ownership have a relationship with the use of financing patterns, while education has no effect.